Antecedent and Consequence the Human Resources Management Factors on Civil Servant Performance - Jumady, Edy; Lilla, L. (Manunggal Halim Jaya, 2021)
This study aims to analyze the effect of motivation, work environment on performance. This type of research is explanatory research. The research sample is a civil servant at Pare-pare city, Indonesia; Data use purposive random sampling of 40 respondents. The research period was carried out in October - December 2020. The method of analysis in this study was multiple regression analysis. The results of this study indicate that work motivation and work environment have a significant effect on performance. This study proves that both theoretically and previous empirical studies explain that increasing motivation and work environment will improve civil servant performance. To get the best results, an employee needs to balance the ability to perform the task given and the willingness to complete the job. This balance can lead to an increase in productivity and an improvement in inefficiency. Motivated employees can lead to increased productivity and allow an organization to achieve higher levels of output. A healthy workplace environment: workplace culture, creating a happier corporate culture. Every company has its own corporate culture. Great company culture can keep employees productive and even help your company retain the best employees, and happy workers are also more likely to stick around